2013
DOI: 10.2478/pjvs-2013-0064
|View full text |Cite
|
Sign up to set email alerts
|

The expression of mitochondrial, cytoplasmic and extracellular superoxide dismutase in the colonic wall of pigs suffering from swine dysenteria

Abstract: The expression of 3 types of peroxide dismutase (SOD1, SOD2 and SOD3) was studied with Real-Time PCR in the colonic wall of domestic pig suffering from swine dysentery. The expression of enzymes was studied separately in the mucosa and the muscular membrane. It was found that in the mucosa the expression of SOD1 (cytoplasmic) did not change, while the levels of expression of mitochondrial SOD2 and extracellular SOD3 were raised in inflamed colon. More dramatic changes were seen in the muscular mebrane where ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…In the previous paper we have also described the changes in the expression of three superoxide dismutases in the mucosa/submucosa, as well as in the tunica muscularis in pigs suffering from swine dysentery (the same individuals as described in the present paper), and found that no changes in the expression of SOD1 and SOD were detected in the mucosa/submucosa layer and expression of SOD3 raised significantly. In the muscular layer all SOD gene expression was raised significantly in dysenteric animals (5). The expression of some other genes, among them COX-2, which is involved in the development of inflammation (unpublished results), were studied, and an increase in COX-2 expression in colitis, as expected, was found.…”
Section: Discussionmentioning
confidence: 81%
“…In the previous paper we have also described the changes in the expression of three superoxide dismutases in the mucosa/submucosa, as well as in the tunica muscularis in pigs suffering from swine dysentery (the same individuals as described in the present paper), and found that no changes in the expression of SOD1 and SOD were detected in the mucosa/submucosa layer and expression of SOD3 raised significantly. In the muscular layer all SOD gene expression was raised significantly in dysenteric animals (5). The expression of some other genes, among them COX-2, which is involved in the development of inflammation (unpublished results), were studied, and an increase in COX-2 expression in colitis, as expected, was found.…”
Section: Discussionmentioning
confidence: 81%
“…Regarding the antioxidant defense mechanisms, we observed here that the expression of the SOD2 gene was also increased in the SDP-PDP group compared to both the SDP and CON groups. This mitochondrial enzyme is considered the rst defense against reactive oxygen species (ROS) formed during normal cell metabolism [31]. Elimination of ROS by SOD2 can be considered as an antiin ammatory effect due to the important role that ROS plays in triggering and promoting in ammation [63].…”
Section: Discussionmentioning
confidence: 99%
“…A list of 56 genes related to intestinal health were selected according to the bibliography [19][20][21][22][23][24][25][26][27][28][29][30][31][32] and included: (1) genes participating in the barrier function (OCLN, ZO1, CLDN1, CLDN4, CLDN15, MUC2, MUC13 and TFF3); (2) genes that play an important role in the immune response, such as pattern recognition receptors, cytokines, chemokines and stress proteins (TLR2, TLR4, IL1B, IL6, IL8, IL10, IL17A, IL22, IFNG, TNF, TGFB1, CCL20, CXCL2, IFNGR1, HSPB1, HSPA4, REG3G, PPARGC1A, FAXDC2 and GBP1);…”
Section: Open Array Designmentioning
confidence: 99%
“…Upregulation of these genes suggests a potential improvement on the capacity for intestinal nutrient uptake and transport. Likewise, the observed upregulation of the SOD gene suggests an effect on the antioxidant system [37]. The IFN-γ gene was downregulation in the BPC compared to the Control group, and this may be positively related to the innate immune response [34], as auto-regulatory loop of local in ammation [38].…”
Section: Prenatal Effects Of Bpc On Sows and Their Offspringmentioning
confidence: 99%